Cost comparisons of five leading brands of the Antiplatelet drug, Clopidogrel, available in an Indian town - Rajadnya, Vikram A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Antiplatelet drugs need to be prescribed lifelong, for most of the selected patients, once started. Price disparity can lead to large financial stress on the patients, especially when cost related aspects are not paid heed to by the prescribing physician. This study was conducted to compare the cost, to the patient, of five most commonly prescribed preparations of different brands of Clopidogrel seventy five milligram, in Kolhapur city. Methods: The present study was undertaken during February 2019 to June 2019. Authors purchased a strip of 10 tablets each of the five leading brands of Clopidogrel seventy five milligram. The prices of the strip of 10 tablets of each of the five chosen brands were compared. Finally, the yearly cost of each of these five different preparations, was compared directly as well as using percentages. The data was collected, analyzed and presented in tabular forms and figures. Results: The data of the cost of five different brands of a single antiplatelet drug, Clopidogrel seventy five milligram shows that the annual cost of the costliest among the five brands of this drug is almost three times that of the cheapest brand, or in other words almost 300 percent that of the cheapest brand. Conclusions: The cost differences between the five brands were not negligible. India, with a major part of the population being very sensitive to the cost of medications, the prescribing physician must select the preparation wisely. The most costly preparation of Clopidogrel can significantly add to the the financial stress on the patient’s yearly expenditure. Thus, Pharmaco economic considerations must take a front seat while making a decision to prescribe medicines, especially in a country like India.